Preservation of auditory P300-like potentials in cortical deafness. - Marianna Cavinato (Public Library of Science (PLoS), 2012)
The phenomenon of blindsight has been largely studied and refers to residual abilities of blind patients without an acknowledged visual awareness. Similarly, "deaf hearing" might represent a further example of dissociation between detection and perception of sounds. Here we report the rare case of a patient with a persistent and complete cortical deafness caused by damage to the bilateral temporo-parietal lobes who occasionally showed unexpected reactions to environmental sounds despite she denied hearing. We applied for the first time electrophysiological techniques to better understand auditory processing and perceptual awareness of the patient. While auditory brainstem responses were within normal limits, no middle- and long-latency waveforms could be identified. However, event-related potentials showed conflicting results. While the Mismatch Negativity could not be evoked, robust P3-like waveforms were surprisingly found in the latency range of 600-700 ms. The generation of P3-like potentials, despite extensive destruction of the auditory cortex, might imply the integrity of independent circuits necessary to process auditory stimuli even in the absence of consciousness of sound. Our results support the reverse hierarchy theory that asserts that the higher levels of the hierarchy are immediately available for perception, while low-level information requires more specific conditions. The accurate characterization in terms of anatomy and neurophysiology of the auditory lesions might facilitate understanding of the neural substrates involved in deaf-hearing.